2017
DOI: 10.3390/nu9040417
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and Potassium Intake in Healthy Adults in Thessaloniki Greater Metropolitan Area—The Salt Intake in Northern Greece (SING) Study

Abstract: A reduction in population sodium (as salt) consumption is a global health priority, as well as one of the most cost-effective strategies to reduce the burden of cardiovascular disease. High potassium intake is also recommended to reduce cardiovascular disease. To establish effective policies for setting targets and monitoring effectiveness within each country, the current level of consumption should be known. Greece lacks data on actual sodium and potassium intake. The aim of the present study was therefore to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 30 publications
8
52
1
1
Order By: Relevance
“…As the habitual salt intake in most countries in the world is close to 10 g per day, 55‐58 an average reduction of 60% per day, as in our meta‐analysis, would lead to the achievement of the recommended target of 5 g or lower per day for the population 55 : this observation suggests that the results of our study could be applicable to real life conditions and are relevant to population‐based strategies for reduction of salt intake 59 …”
Section: Discussionsupporting
confidence: 54%
“…As the habitual salt intake in most countries in the world is close to 10 g per day, 55‐58 an average reduction of 60% per day, as in our meta‐analysis, would lead to the achievement of the recommended target of 5 g or lower per day for the population 55 : this observation suggests that the results of our study could be applicable to real life conditions and are relevant to population‐based strategies for reduction of salt intake 59 …”
Section: Discussionsupporting
confidence: 54%
“…In line with this notion, previous studies have shown more protein and sodium intake in men than in women (44,45). Moreover, a recent study showed that there was a considerable variation in potassium intake between men and women among 252 healthy Greek adults (46). Notably, a previous study suggested a possible role of estrogen in the lower plasma potassium level in female rodents (47).…”
Section: Discussionmentioning
confidence: 71%
“…While small phase II clinical trials, such as DASH-Sodium,40 have achieved these targets in the short term, they required complete control of dietary intake, which is impractical in free living populations. In contrast, the PREDIMED study,43 which promoted increased intake of potassium containing foods (fruit, vegetables, nuts) with greater adherence to the Mediterranean diet, without focusing on low sodium intake, reported a statistically significant reduction in cardiovascular disease and mortality, and adherence to a Mediterranean diet has an inconsistent correlation with sodium intake 4445. In addition, a recent analysis of the NHANES study reported that sodium intake >2.3 g/day was associated with better diet quality, compared with diets of less than 2.3 g/day, meaning that improving dietary quality is likely to be easier to achieve within a moderate sodium intake range 46.…”
Section: Discussionmentioning
confidence: 90%